IMPLEMENTASI METODE DISTRIBUTION REQUIREMENT PLANNING UNTUK MEMINIMALKAN BIAYA DISTRIBUSI DI PT DBM CABANG PURWOKERTO - Kisanjani, Alex; Wahyuni, Hendang Sri; Andivas, Marulan; Misrianto, Misrianto (Indragiri Islamic University, 2022)
Distribution is one of the most important things to increase customer satisfaction. However, distribution is often a problem for companies. The wider the marketing area owned by the company, the more complex the problems that arise in the distribution schedule. PT DBM's Purwokerto branch also faced a similar situation, where distribution activities were not well coordinated, resulting in lost sales, accumulation of goods in each warehouse and swelling storage costs. Therefore, an appropriate method is needed to schedule distribution activities to each warehouse, so as to reduce distribution costs. The method used in this research is Distribution Requirement Planning. This method is effective for reducing distribution costs. The results showed that by using the Distribution Requirement Planning method, distribution costs were lower than the company's distribution method. Distribution costs using the company distribution method amounted to Rp. 1,371,391, while distribution costs using the Distribution Requirements Planning method amounted to Rp. 1,040,501, resulting in a cost reduction of 24.13%.